SISTEM KONTROL DAN MONITORING ENERGI LAMPU PINTAR MENGGUNAKAN APLIKASI BERBASIS INTERNET OF THINGS - Shalilla Farrah Sahita; Muhammad Distya Rizky; Indra Dwisaputra; Nofriyani Nofriyani (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Along with the development of increasingly capable technology, people's daily lives can be helped by the presence of smart devices. The most widely used smart devices are smartphones. In this study, a smartphone is used as a device to control artificial lighting in the form of lamps. If lamps generally use an electric switch to turn on and off, this control system allows smartphones to be used as real-time light on-off control remotely using the Internet of Things (IoT). The control system is programmed using Arduino IDE and using NodeMCU ESP8266 microcontroller. This system can be run using a smart home application that connects users with smart lamps. The application is created using Mit App Inventor and the data is stored in a database that is Firebase. In addition, there is a monitoring system to monitor the use of power, energy, voltage, electric current, and conversion of electricity usage costs in lamps through applications found on smartphones and also Firebase.